Starch-based pressure-sensitive adhesive, preparation method and application thereof, and thermal sensitive paper self-adhesive
Patent Information
- Application Number
- CN202611162697.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-10-27
AI Technical Summary
但是相关的乳液型丙烯酸酯压敏胶存在接枝效率和环保降解速率不能平衡的问题
本发明中,所述氧化淀粉与丙烯酸酯类单体体系的质量比为1:2.7~1:3.3,能满足接枝效率和环保降解速率的需求平衡,避免过高丙烯酸酯类单体的使用质量,在该特定质量比下,体系具有适中的接枝率(70%~140%),一方面,在淀粉主链上生长的聚丙烯酸酯接枝侧链与游离的均聚物相互缠结,形成了具有适宜黏弹性的三维网络,既克服了接枝率过低导致的内聚强度不足、持粘力差的问题,又避免了接枝率过高引起的网络过度刚化、初粘力下降的缺陷;另一方面,该比例控制了石化基组分的整体占比,且适中的接枝率保留了淀粉主链的非晶区与暴露位点,避免了致密聚丙烯酸酯膜对淀粉的过度包裹,使水分和微生物能够有效渗透并降解淀粉骨架,从而实现了粘结性能与环保降解性能的完美平衡。衣康酸作为功能单体引入羧基(-COOH),一方面提高压敏胶对极性表面的润湿性,另一方面为后续柠檬酸/酒石酸交联提供反应位点,甲基丙烯酸羟乙酯引入羟基(-OH),增强压敏胶的内聚强度和交联密度,两者协同作用使压敏胶在保持初粘力的同时具有足够的持粘力;氢化松香甘油酯替代传统的石油基增粘树脂,配合APG生物基乳化剂,使增粘树脂体系具有生物基来源和可降解性;柠檬酸和酒石酸均为天然有机酸,分子中含多个羧基和羟基,可与氧化淀粉分子链上的羟基以及IA和HEMA引入的官能团形成氢键和酯键交联,构建三维交联网络,该交联体系在压敏胶使用阶段提供足够的内聚强度,在堆肥降解条件下可被微生物分解,区别于传统的异氰酸酯或环氧类不可降解交联剂;采用过硫酸盐-无机硫系还原剂构成氧化还原引发剂体系,属于水溶性氧化还原引发剂,在60~65℃的较低温度下产生自由基,有效降低接枝反应温度,避免高温导致淀粉回生或单体均聚加剧,同时减少能源消耗。且氢化松香甘油酯的软化点为80~85℃,与丙烯酸酯共聚物的相容性良好,可有效提升压敏胶的初粘力和剥离强度。且本发明的制备方法操作简单,适于实现工业化应用。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of self-adhesive label materials and products, and in particular to a starch-based pressure-sensitive adhesive, its preparation method and application, and thermal paper self-adhesive. Background Technology
[0002] Thermal paper self-adhesive labels are widely used in logistics, retail, medical, and food packaging. Traditional thermal paper self-adhesive products typically consist of a three-layer structure: thermal paper face stock, pressure-sensitive adhesive, and glassine release paper. The pressure-sensitive adhesive mainly uses hot-melt pressure-sensitive adhesive or emulsion-type acrylic pressure-sensitive adhesive. Hot-melt pressure-sensitive adhesives experience a significant decrease in adhesive strength and cohesion at high temperatures; the adhesive layer may soften, creep, or even fail at higher temperatures, limiting its application. In contrast, emulsion-type acrylic pressure-sensitive adhesives are starch-grafted monomer copolymers made from a starch matrix and grafted monomers. Grafted monomers are used to graft copolymerize onto the surface of starch molecules, embedding biodegradable starch segments into the resulting long polymer chains, thus achieving biodegradable pressure sensitivity. However, these emulsion-type acrylic pressure-sensitive adhesives suffer from an imbalance between grafting efficiency and environmental degradation rate. Summary of the Invention
[0003] In view of this, the purpose of this invention is to provide a starch-based pressure-sensitive adhesive, its preparation method and application, and a thermal paper self-adhesive. The starch-based pressure-sensitive adhesive prepared by this invention can meet the requirements of grafting efficiency and environmental degradation rate.
[0004] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a method for preparing starch-based pressure-sensitive adhesive, comprising the following steps: Oxidized starch is gelatinized and activated to obtain a starch-based material system; The starch-based system, acrylate monomer system, itaconic acid (IA), hydroxyethyl methacrylate (HEMA), and initiator system are mixed and subjected to a free radical graft copolymerization reaction to obtain a graft copolymer emulsion, wherein the grafting rate of the graft copolymer in the graft copolymer emulsion is 70%~140%; The graft copolymer emulsion, the tackifying resin system and the biodegradable crosslinking agent are mixed and crosslinked to obtain the starch-based pressure-sensitive adhesive. The mass ratio of oxidized starch to acrylate monomer system used in preparing the starch base material system is 1:2.7 to 1:3.3; the acrylate monomer system includes butyl acrylate (BA), isooctyl acrylate (2-EHA) and methyl methacrylate (MMA). The initiator system includes persulfate and inorganic sulfur-based reducing agents; The tackifying resin system includes hydrogenated rosin glycerol ester and a bio-based nonionic emulsifier (APG bio-based emulsifier). The degradable crosslinking agents include citric acid and tartaric acid.
[0005] Preferably, the mass ratio of oxidized starch, butyl acrylate, isooctyl acrylate and methyl methacrylate is 18~22:35~45:12~19:2~9.
[0006] Preferably, the mass ratio of oxidized starch to itaconic acid is 18~22:2~3.
[0007] Preferably, the mass ratio of oxidized starch to hydroxyethyl methacrylate is 18~22:1.5~2.5.
[0008] Preferably, the bio-based nonionic emulsifier comprises dodecyl glycoside and / or tetradecyl glycoside.
[0009] The present invention also provides a starch-based pressure-sensitive adhesive prepared by the preparation method described above, wherein the grafting rate of the starch-based pressure-sensitive adhesive is 70%~140%.
[0010] This invention also provides the application of the starch-based pressure-sensitive adhesive described above in the field of thermal paper self-adhesive.
[0011] The present invention also provides a thermal paper self-adhesive, comprising a biaxially oriented polylactic acid (BOPLA) film protective layer, a starch-based coating layer, a thermal color layer, a starch-based pre-coating layer, a thermal base paper, a starch-based pressure-sensitive adhesive layer, a solvent-free silicone oil layer, and glassine paper stacked sequentially, wherein the starch-based coating layer and the starch-based pressure-sensitive adhesive layer contain the starch-based pressure-sensitive adhesive described in the above technical solution.
[0012] Preferably, the thermosensitive color-developing layer comprises 3-(3-tolylureo)phenyl-4-methylbenzenesulfonate (PF201).
[0013] Preferably, the starch-based pre-coating comprises modified starch, filler, and lubricant.
[0014] This invention provides a method for preparing a starch-based pressure-sensitive adhesive, comprising the following steps: gelatinizing and activating oxidized starch to obtain a starch-based material system; mixing the starch-based material system, an acrylate monomer system, itaconic acid, hydroxyethyl methacrylate, and an initiator system to conduct a free radical graft copolymerization reaction to obtain a graft copolymer emulsion, wherein the grafting rate of the graft copolymer in the graft copolymer emulsion is 70%~140%; mixing the graft copolymer emulsion, a tackifying resin system, and a biodegradable crosslinking agent to conduct a crosslinking reaction to obtain the starch-based pressure-sensitive adhesive; the mass ratio of oxidized starch to the acrylate monomer system used in preparing the starch-based material system is 1:2.7~1:3.3; the acrylate monomer system includes butyl acrylate, isooctyl acrylate, and methyl methacrylate; the initiator system includes ammonium persulfate and sodium bisulfite; the tackifying resin system includes hydrogenated rosin glycerol ester and a bio-based nonionic emulsifier; and the biodegradable crosslinking agent includes citric acid and tartaric acid.
[0015] Compared with the prior art, the beneficial effects of the present invention are as follows: In this invention, the mass ratio of oxidized starch to acrylate monomer system is 1:2.7 to 1:3.3, which satisfies the balance between grafting efficiency and environmental degradation rate, avoiding excessive use of acrylate monomers. At this specific mass ratio, the system has a moderate grafting rate (70% to 140%). On the one hand, the polyacrylate grafted side chains grown on the starch backbone entangle with the free homopolymer, forming a three-dimensional network with suitable viscoelasticity. This overcomes the problems of insufficient cohesive strength and poor adhesion caused by too low a grafting rate, and avoids the defects of excessive network rigidity and decreased initial adhesion caused by too high a grafting rate. On the other hand, this ratio controls the overall proportion of petrochemical-based components, and the moderate grafting rate retains the amorphous regions and exposed sites of the starch backbone, avoiding excessive encapsulation of starch by the dense polyacrylate film. This allows moisture and microorganisms to effectively penetrate and degrade the starch skeleton, thus achieving a perfect balance between adhesive performance and environmental degradation performance. Itaconic acid, as a functional monomer, introduces carboxyl groups (-COOH), which improves the wettability of the pressure-sensitive adhesive to polar surfaces and provides reaction sites for subsequent citric acid / tartaric acid crosslinking. Hydroxyethyl methacrylate introduces hydroxyl groups (-OH), enhancing the cohesive strength and crosslinking density of the pressure-sensitive adhesive. The synergistic effect of these two components allows the pressure-sensitive adhesive to maintain sufficient holding power while retaining initial tack. Hydrogenated rosin glycerol ester replaces traditional petroleum-based tackifying resins, and in combination with APG bio-based emulsifiers, gives the tackifying resin system a bio-based origin and biodegradability. Citric acid and tartaric acid are both natural organic acids containing multiple carboxyl and hydroxyl groups in their molecules. It can form hydrogen bonds and ester bonds with the hydroxyl groups on the oxidized starch molecular chain and the functional groups introduced by IA and HEMA to construct a three-dimensional cross-linked network. This cross-linked system provides sufficient cohesive strength during the application stage of the pressure-sensitive adhesive and can be decomposed by microorganisms under composting degradation conditions, unlike traditional isocyanates or epoxy-based non-degradable cross-linking agents. A persulfate-inorganic sulfur-based reducing agent is used to construct a redox initiator system, which is a water-soluble redox initiator. It generates free radicals at a relatively low temperature of 60-65℃, effectively reducing the grafting reaction temperature and avoiding high-temperature-induced starch retrogradation or accelerated monomer homopolymerization, while also reducing energy consumption. Furthermore, the softening point of hydrogenated rosin glycerol ester is 80-85℃, and it has good compatibility with acrylate copolymers, effectively improving the initial tack and peel strength of the pressure-sensitive adhesive. The preparation method of this invention is simple to operate and suitable for industrial application.
[0016] Traditional thermal paper self-adhesive products use bisphenol A (BPA) or bisphenol S (BPS) as color developers in the thermal paper surface layer, styrene-butadiene latex or polyvinyl alcohol adhesive in the pre-coating layer, and a coating containing polyethylene wax in the protective layer. This invention also provides a thermal paper self-adhesive that (1) completely replaces BPA / BPS color developers by using a non-phenolic color developer PF201 (3-(3-tolylureo)phenyl-4-methylbenzenesulfonate) to ensure food contact safety compliance; (2) uses starch-based adhesives to replace traditional styrene-butadiene latex. (3) The protective layer uses BOPLA film instead of traditional polyethylene wax coating to achieve bio-based compostable degradation of the protective layer; (4) The starch-based pressure-sensitive adhesive layer uses oxidized cassava grafted acrylate copolymer system. By introducing itaconic acid and hydroxyethyl methacrylate functional monomers, hydrogenated rosin glycerol ester and bio-based nonionic emulsifier tackifying resin system and citric acid / tartaric acid degradable crosslinking system, the degradability and pressure-sensitive performance of the pressure-sensitive adhesive are balanced; (5) The proportion of degradable materials in the overall product exceeds 90%, which meets the EN 13432 industrial composting certification requirements. Detailed Implementation
[0017] This invention provides a method for preparing starch-based pressure-sensitive adhesive, comprising the following steps: Oxidized starch is gelatinized and activated to obtain a starch-based material system; The starch-based system, acrylate monomer system, itaconic acid (IA), hydroxyethyl methacrylate (HEMA), and initiator system are mixed and subjected to a free radical graft copolymerization reaction to obtain a graft copolymer emulsion, wherein the grafting rate of the graft copolymer in the graft copolymer emulsion is 70%~140%; The graft copolymer emulsion, the tackifying resin system and the biodegradable crosslinking agent are mixed and crosslinked to obtain the starch-based pressure-sensitive adhesive. The mass ratio of oxidized starch to acrylate monomer system used in preparing the starch-based material system is 1:2.7 to 1:3.3; the acrylate monomer system includes butyl acrylate, isooctyl acrylate, and methyl methacrylate. The initiator system includes persulfate and inorganic sulfur-based reducing agents; The tackifying resin system includes hydrogenated rosin glycerol ester and a bio-based nonionic emulsifier; The degradable crosslinking agents include citric acid and tartaric acid.
[0018] Unless otherwise specified, all raw materials used in this invention are commercially available products in the field.
[0019] This invention gelatinizes and activates oxidized starch to obtain a starch-based material system.
[0020] In this invention, the oxidized starch preferably includes oxidized cassava starch.
[0021] In this invention, the oxidized starch is preferably mixed with water to perform the gelatinization and activation, wherein the gelatinization is in situ gelatinization.
[0022] In this invention, the preferred mass ratio of oxidized starch to water is 18~22:56~70.
[0023] In this invention, the gelatinization and activation preferably include the following steps: mixing the oxidized starch with water, turning on the stirring (preferably at a speed of 150~200 rpm), heating to 85~90℃ and holding for 30~40 min to allow the oxidized starch to fully gelatinize and swell, with the straight / branched molecules unfolding and exposing the active sites of hydroxyl and carboxyl groups, and then cooling to 55~60℃, at which temperature the starch molecular chains still maintain high activity and are below the self-polymerization critical temperature of acrylate monomers.
[0024] After obtaining the starch-based material system, the present invention mixes the starch-based material system, the acrylate monomer system, itaconic acid, hydroxyethyl methacrylate, and the initiator system to carry out a free radical graft copolymerization reaction to obtain a graft copolymer emulsion. The grafting rate of the graft copolymer in the graft copolymer emulsion is 70%~140%. The mass ratio of oxidized starch to the acrylate monomer system used to prepare the starch-based material system is 1:2.7~1:3.3. The acrylate monomer system includes butyl acrylate, isooctyl acrylate, and methyl methacrylate. The initiator system includes persulfate and an inorganic sulfur-based reducing agent. The free radical graft copolymerization reaction uses persulfate as an initiator to generate free radical active sites on the oxidized starch molecular chain, thereby initiating the polymerization of the acrylate monomers to form a starch-acrylate graft copolymer.
[0025] In this invention, the mass ratio of oxidized starch to acrylate monomer system can be specifically 1:2.7, 1:2.9, or 1:3.3. If the mass ratio is too low, the pressure-sensitive adhesive will have too low viscoelasticity and will not be able to meet the most basic adhesion requirements. If too much acrylate monomer system is used, the grafting efficiency will decrease. To achieve high grafting efficiency, more acrylate needs to be added, but the proportion of biodegradable components will decrease. A ratio of 1:2.7 to 1:3.3 means that the final adhesive contains 23% to 27% bio-based (starch) and 73% to 77% petrochemical-based (acrylate). At this ratio, the monomer concentration is moderate, which can ensure that enough acrylate homopolymer / graft copolymer is generated to form a viscous network, and also allow the starch free radicals generated by the initiator to have enough monomers for chain growth.
[0026] In this invention, the preferred mass ratio of oxidized starch, butyl acrylate, isooctyl acrylate, and methyl methacrylate is 18~22:35~45:12~19:2~9, specifically 20:38:15:5, 18:35:12:2, or 22:45:19:9. Limiting the mass ratio of oxidized starch, butyl acrylate, isooctyl acrylate, and methyl methacrylate to the above range can synergistically regulate the glass transition temperature and viscoelastic network of the graft copolymer emulsion, achieving effective coordination of soft and hard monomers. Specifically, butyl acrylate and isooctyl acrylate, as soft monomers, impart good softness, wettability to the surface of the adhered object, and excellent initial tack to the colloid; methyl methacrylate, as a hard monomer, can effectively improve the cohesive strength, creep resistance, and water resistance of the colloid; this specific ratio ensures good graft compatibility with the oxidized starch backbone while giving the copolymer side chains suitable flexibility and rigidity, thus enabling the pressure-sensitive adhesive to maintain high initial tack and peel strength while also possessing excellent holding power and water resistance.
[0027] In this invention, the preferred mass ratio of oxidized starch to itaconic acid is 18-22:2-3, specifically 20:2.5, 18:2.5, or 22:2.5. Limiting the mass ratio of oxidized starch to itaconic acid within the above range can effectively introduce an appropriate amount of carboxyl functional groups. This improves the wettability of the pressure-sensitive adhesive to the surface of polar adherends and provides sufficient esterification reaction sites for subsequent degradable crosslinking agents. At the same time, it avoids the increase in polymer chain rigidity and excessive crosslinking due to excessive itaconic acid, thereby preventing a decrease in initial tack and achieving a good balance between wettability, degree of crosslinking, and initial tack performance.
[0028] In this invention, the preferred mass ratio of oxidized starch to hydroxyethyl methacrylate is 18-22:1.5-2.5, specifically 20:2, 18:2, or 22:2. Limiting the mass ratio of oxidized starch to hydroxyethyl methacrylate within the above range effectively introduces an appropriate amount of hydroxyl functional groups. This significantly enhances the cohesive strength and crosslinking density of the pressure-sensitive adhesive's three-dimensional network to improve tack, while avoiding excessive crosslinking and brittleness of the colloid due to excessive hydroxyethyl methacrylate content. This prevents a significant decrease in peel strength and initial tack, achieving the best balance between cohesive strength and adhesive performance.
[0029] In this invention, the persulfate preferably includes one or more of ammonium persulfate (APS), potassium persulfate (KPS), and sodium persulfate (NaPS), more preferably ammonium persulfate; the inorganic sulfur-based reducing agent preferably includes one or more of sodium bisulfite (SBS), sodium metabisulfite, sodium sulfite, sodium dithionite, and sodium thiosulfate, more preferably sodium bisulfite.
[0030] In this invention, the preferred mass ratio of oxidized starch to ammonium persulfate is 18-22:0.3-0.5, specifically 20:0.4, 18:0.4, or 22:0.4. Limiting the mass ratio of oxidized starch to ammonium persulfate within this range effectively controls the concentration of free radicals and the initiation rate in the reaction system, achieving a balance between grafting and homopolymerization, and protecting the starch backbone from excessive oxidative degradation. Specifically, within this mass ratio range, sufficient primary free radicals are generated to abstract hydrogen from the starch hydroxyl groups, thereby generating sufficient starch macromolecular free radicals to initiate acrylate monomer grafting, ensuring a high monomer conversion rate and forming an effective viscoelastic network with a moderate grafting rate (70%-140%). Furthermore, it avoids the intensification of the aqueous homopolymerization reaction of acrylates and the excessive oxidation and chain breakage of the starch backbone due to excessive initiator concentration, thus maintaining the molecular weight and physical entanglement ability of the starch skeleton. This results in a good balance between initial tack, peel strength, and holding power in the prepared pressure-sensitive adhesive, while also ensuring a high biodegradability rate.
[0031] In this invention, the preferred mass ratio of oxidized starch to sodium bisulfite is 18-22:0.1-0.2, specifically 20:0.15, 18:0.15, or 22:0.15. Limiting the mass ratio of oxidized starch to sodium bisulfite within this range effectively controls the concentration of the reducing agent in the redox initiation system, ensuring the synergistic generation of appropriate and mild primary free radicals with ammonium persulfate, thereby optimizing the microenvironment of the grafting reaction. Specifically, sodium bisulfite, as a reducing agent, can significantly reduce the decomposition activation energy of ammonium persulfate, enabling the graft copolymerization reaction to proceed efficiently at a lower temperature of 60-65°C, avoiding starch gelatinization retrogradation and intensified homopolymerization of acrylate monomers caused by high temperatures. Simultaneously, limiting the ratio within this range ensures sufficient free radicals to maintain high grafting efficiency while preventing chain transfer side reactions caused by excessive reducing agent or polymer molecular weight reduction due to over-reduction, thus guaranteeing the cohesive strength and excellent holding power of the pressure-sensitive adhesive network.
[0032] In this invention, the preferred mass ratio of ammonium persulfate to sodium bisulfite is 2:1 to 3:1, specifically 8:3. Limiting the mass ratio of ammonium persulfate to sodium bisulfite within this range allows for precise control of the generation rate and half-life of free radicals in the redox initiation system, achieving a competitive balance between the grafting reaction and the homopolymerization reaction. At this specific mass ratio, ammonium persulfate and sodium bisulfite undergo a single-electron transfer redox reaction, releasing primary free radicals at a suitable and stable rate. This effectively captures hydrogen from the hydroxyl groups of starch to generate starch macromolecular free radicals to initiate grafting, maintaining a moderate grafting rate (70% to 140%). It also avoids excessively rapid free radical generation leading to explosive polymerization, gelation, or accelerated homopolymerization of the acrylate aqueous phase, thereby ensuring the stability and film uniformity of the graft copolymer emulsion. This results in an optimal balance between initial tack, peel strength, and degradation performance in the prepared pressure-sensitive adhesive.
[0033] In this invention, the preferred temperature for the free radical graft copolymerization reaction is 60-65°C, and the preferred holding time is 1.5-2 hours. The holding time is calculated from the time the raw materials are completely added.
[0034] In this invention, BA, 2-EHA, MMA, IA, and HEMA are pre-mixed into monomer phases. APS is dissolved in a first water to obtain an APS solution, and SBS is dissolved in a second water to obtain an SBS solution. These are set aside separately. A portion of the monomer phases is first mixed with the starch-based material system. The remaining monomer phases are then added dropwise to the resulting mixture. One hour after the addition of the remaining monomer phases begins, the APS solution and SBS solution are simultaneously added dropwise to carry out the free radical graft copolymerization reaction.
[0035] In this invention, the mass ratio of APS to the first water is preferably 1:5; the mass ratio of SBS to the second water is preferably 1:3.
[0036] In this invention, the preferred mass of a portion of the monomer phase is 30% of the total monomer phase. This portion serves as a base material in the initial stage of the reaction, providing a suitable initial monomer concentration for the graft copolymerization reaction, thereby smoothly initiating the reaction and suppressing explosive polymerization. Specifically, this portion of the monomer phase is pre-mixed with oxidized starch and an initiator, which allows grafting to preferentially occur around the free radicals of the starch macromolecules in the initial stage of the reaction, forming a preliminary grafted side chain backbone. This not only effectively buffers the intense exothermic reaction during acrylate polymerization, preventing gelation or explosive polymerization caused by local overheating, but also provides steric hindrance and chain growth templates for the subsequently added monomers, thereby significantly suppressing the homopolymerization side reaction of acrylate monomers in the aqueous phase, improving grafting efficiency, and ensuring uniform particle size distribution and film stability of the final graft copolymer emulsion.
[0037] In this invention, the first mixing time is preferably 15 minutes, so that the monomer diffuses between starch molecular chains.
[0038] The present invention preferably incorporates the monomer phase into the starch-based material system.
[0039] In this invention, the preferred dripping time for the APS solution is 2.5 to 3 hours; the preferred dripping time for the SBS solution is 1.5 to 2 hours.
[0040] In this invention, APS is preferably added during the free radical graft copolymerization process to eliminate residual monomers, and the mass ratio of oxidized starch to added APS is preferably 18~22:0.05.
[0041] After obtaining the graft copolymer emulsion, the present invention mixes the graft copolymer emulsion, the tackifying resin system and the biodegradable crosslinking agent to carry out a crosslinking reaction to obtain the starch-based pressure-sensitive adhesive.
[0042] In this invention, the crosslinking reaction is preferably carried out at room temperature, i.e., no additional heating or cooling is required.
[0043] In this invention, the bio-based nonionic emulsifier preferably includes dodecyl glycoside and / or tetradecyl glycoside, is 100% bio-based, non-toxic and readily biodegradable.
[0044] In this invention, the preferred mass ratio of the hydrogenated rosin glycerol ester to the bio-based nonionic emulsifier is 8~12:0.3~0.5, specifically 10:0.4. Limiting the mass ratio of the hydrogenated rosin glycerol ester to the bio-based nonionic emulsifier to the above range can effectively control the emulsification and dispersion state and interfacial compatibility of the hydrophobic tackifying resin in the aqueous system, thereby achieving a balance between the tackifying effect and the cohesive strength of the colloid. Specifically, within this mass ratio range, the bio-based nonionic emulsifier can fully emulsify hydrogenated rosin glycerol ester into a nano-scale fine emulsion, allowing it to be uniformly blended with the starch-based graft copolymer emulsion. This results in the formation of a uniform interpenetrating network during film formation, significantly improving the wettability and initial tack of the colloid on the surface of the adhered object. Simultaneously, this ratio avoids resin agglomeration and stratification due to insufficient emulsifier dosage, and also prevents a decrease in the water resistance and cohesive strength of the colloid caused by excessive free emulsifier, ensuring the stability of the overall bonding performance and environmental degradation performance of the pressure-sensitive adhesive. The use of hydrogenated rosin glycerol ester to replace traditional petroleum-based tackifying resin, combined with APG bio-based emulsifier, gives the tackifying resin system a bio-based origin and biodegradability. The hydrogenated rosin glycerol ester has a softening point of 80-85℃ and good compatibility with acrylate copolymers, effectively improving the initial tack and peel strength of the pressure-sensitive adhesive.
[0045] In this invention, the tackifying resin system preferably further includes water, and the mass ratio of the hydrogenated rosin glycerol ester to water is preferably 8~12:15~20.
[0046] In this invention, the hydrogenated rosin glycerol ester is heated and melted (120°C), and water and APG are added at 70°C. The mixture is then sheared and emulsified for 10 minutes to obtain the thickening resin system.
[0047] In this invention, the preferred mass ratio of oxidized starch to hydrogenated rosin glycerol ester is 18~22:8~12, specifically 20:10, 18:10 or 22:10. Limiting the mass ratio of oxidized starch to hydrogenated rosin glycerol ester within the above range can effectively control the compatibility and microphase separation between the rigid starch skeleton and the tackifying resin in the pressure-sensitive adhesive system, achieving the best balance between the initial tack, peel strength and holding power of the colloid. Specifically, hydrogenated rosin glycerol ester, as a tackifying resin, can effectively penetrate the graft copolymer network at this specific ratio, reducing the surface energy and glass transition temperature of the film, giving the colloid excellent fluidity to quickly wet the surface of the adhered objects, thereby significantly improving initial tack and peel strength. At the same time, this ratio avoids excessive dilution of the rigid starch skeleton and destruction of the physical entanglement network caused by excessive tackifying resin, ensuring that the colloid has excellent creep resistance and cohesive strength (holding power) under stress. While maintaining high adhesion performance, it controls the total proportion of non-starch hydrophobic components, ensuring a high biodegradability rate of the final product.
[0048] In this invention, the preferred mass ratio of citric acid to tartaric acid in the biodegradable crosslinking agent is 0.5~1.0:0.2~0.4, specifically 0.8:0.3. Limiting the mass ratio of citric acid to tartaric acid within the above range can effectively control the crosslinking density and topology of the pressure-sensitive adhesive's three-dimensional crosslinking network, achieving a dynamic balance between the cohesive strength and flexibility of the colloid. Specifically, citric acid, as a tricarboxylic acid, has high multifunctionality and can construct a high-density three-dimensional rigid crosslinking network, significantly improving the colloid's creep resistance and holding power. Tartaric acid, as a dicarboxylic acid, has relatively flexible molecular chains and can impart certain flexible segments to the network when participating in crosslinking, alleviating the excessive rigidity of the network caused by single citric acid crosslinking. By limiting the ratio within the aforementioned range, a suitable crosslinking density is ensured to maintain excellent tack and water resistance, avoiding brittleness, loss of initial tack, and excessive acid degradation of the starch backbone caused by excessive citric acid. It also prevents the colloid from softening due to insufficient crosslinking, leading to cohesive failure (residual adhesive) during peeling. This achieves the optimal viscoelastic balance between initial tack, peel strength, and tack in the pressure-sensitive adhesive. Furthermore, both citric acid and tartaric acid are bio-based small molecules, ensuring the colloidal network can be completely degraded by environmental microorganisms after disposal. Both citric acid and tartaric acid are natural organic acids containing multiple carboxyl and hydroxyl groups, which can form hydrogen bonds and ester bonds with the hydroxyl groups on the starch molecular chain and the functional groups introduced by IA / HEMA to construct a three-dimensional crosslinked network. Anhydrous citric acid is preferred. The degradable crosslinking agent provides sufficient cohesive strength during the use of the pressure-sensitive adhesive and can be decomposed by microorganisms under composting conditions, unlike traditional isocyanates or epoxy-based non-degradable crosslinking agents.
[0049] In this invention, the biodegradable crosslinking agent preferably further includes water, and the mass ratio of citric acid to water is preferably 0.5~1.0:2~3.
[0050] In this invention, the preferred mass ratio of oxidized starch to citric acid is 18~22:0.5~1.0, specifically 20:0.8, 18:0.8 or 22:0.8. Limiting the mass ratio of oxidized starch to citric acid within the above range can effectively control the crosslinking density of the three-dimensional crosslinking network of the pressure-sensitive adhesive, thereby improving the cohesive strength of the adhesive while avoiding acid-catalyzed degradation of the starch skeleton. Specifically, within this mass ratio range, the multiple carboxyl groups of citric acid can undergo moderate esterification and crosslinking with the hydroxyl groups on the oxidized starch backbone and functional monomers to form a dense and stable three-dimensional network. This significantly restricts the slippage of polymer chain segments under stress, giving the colloid excellent creep resistance and holding power. At the same time, this specific ratio avoids the problems of insufficient crosslinking, soft colloid, and poor water resistance caused by too low a crosslinking agent dosage. It also prevents the excessive rigidity of the crosslinked network caused by excessive citric acid (leading to loss of initial tack) and the side reaction of starch glycosidic bond hydrolysis and chain breakage under acidic conditions. This ensures the integrity of the high molecular weight skeleton of the pressure-sensitive adhesive network and achieves the best viscoelastic balance of initial tack, peel strength, and holding power.
[0051] The present invention preferably involves mixing the citric acid, tartaric acid, and water to obtain the biodegradable crosslinking agent.
[0052] In this invention, the tackifying resin system is preferably added to the graft copolymer emulsion under stirring, the temperature is lowered to 45-50°C, and the mixture is stirred for 30 minutes to obtain a blended system. Then, the biodegradable crosslinking agent is added to the blended system, and the mixture is stirred for 15 minutes. The pH value is then adjusted to 6.5-7.0 with ammonia or triethanolamine, an antifoaming agent is added, and the mixture is stirred for 15 minutes. The mixture is then filtered through a 200-mesh filter to obtain the starch-based pressure-sensitive adhesive product.
[0053] In this invention, the defoamer preferably includes one or more of polydimethylsiloxane, polyether-modified organosilicon, and isooctyl alcohol.
[0054] In this invention, the preferred mass ratio of oxidized starch to defoamer is 18-22:0.2-0.4, specifically 20:0.3, 18:0.3, or 22:0.3. Limiting the mass ratio of oxidized starch to defoamer within this range effectively eliminates bubbles generated during gelatinization and emulsion polymerization, ensuring the smoothness and density of the coated film, while avoiding negative impacts on the adhesive properties. Specifically, within this mass ratio range, the defoamer can rapidly destroy microbubbles and inhibit bubble regeneration, avoiding pinholes or adhesive breaks in the film due to insufficient dosage, thereby ensuring the effective contact area between the film and the substrate, maintaining stable initial tack and peel strength. Simultaneously, this specific ratio also prevents problems such as uneven surface tension distribution, coating pinholes, and even localized demulsification and stratification of the emulsion caused by excessive defoamer, ensuring the film uniformity and system stability of the graft copolymer emulsion.
[0055] The present invention does not have a special limitation on the amount of ammonia or triethanolamine used, as long as the pH value can be adjusted to 6.5~7.0.
[0056] This invention also provides a starch-based pressure-sensitive adhesive prepared by the preparation method described above. By adjusting the mass ratio of oxidized starch to acrylate monomers to 1:2.7~1:3.3, this invention can meet the balance requirements of grafting efficiency (70%~140%) and environmental degradation rate, while avoiding excessive use of acrylate monomers.
[0057] This invention also provides the application of the starch-based pressure-sensitive adhesive described above in the field of thermal paper self-adhesive.
[0058] The present invention also provides a thermal paper self-adhesive, comprising, from top to bottom, a biaxially oriented polylactic acid (BOPLA) film protective layer, a starch-based coating layer, a thermal color layer, a starch-based pre-coating layer, a thermal base paper, a starch-based pressure-sensitive adhesive layer, a solvent-free silicone oil layer, and glassine paper, wherein the starch-based coating layer and the starch-based pressure-sensitive adhesive layer contain the starch-based pressure-sensitive adhesive described in the above technical solution.
[0059] In this invention, the BOPLA film protective layer replaces the traditional polyethylene wax coating, and has anti-scratch, waterproof and oil-proof properties. At the same time, the protective layer is bio-based and compostable, ensuring overall biodegradability.
[0060] In this invention, the thickness of the BOPLA film protective layer is preferably 15~25μm, specifically 20μm, and it is biodegradable according to EN 13432 and ASTM D6400, and can be completely degraded into water and carbon dioxide within 12~24 weeks under industrial composting conditions (58°C); the tensile strength of the BOPLA film protective layer is preferably ≥70MPa, the elongation is preferably ≥50%, and the heat sealing initiation temperature is preferably 80~100°C.
[0061] In this invention, the starch-based pre-coating preferably includes modified starch, fillers, and lubricants.
[0062] In this invention, the filler preferably comprises kaolin.
[0063] In this invention, the lubricant preferably comprises zinc stearate.
[0064] In this invention, the modified starch preferably includes phosphated starch (starch phosphate) and / or acetate starch.
[0065] In this invention, the gelatinization temperature of the modified starch is preferably 60~75℃, which can form a porous pre-coating layer, ensuring adhesion to the thermal base paper and providing a good bonding interface for the thermal color layer. The surface strength (roughing speed) of the starch-based pre-coating is preferably not less than 1.0m / s, more preferably not less than 2.0m / s, and the surface strength is measured by an IGT printability tester.
[0066] In this invention, the preferred mass ratio of the modified starch, filler and lubricant is 20~40:60~80:2~5, which ensures that the starch-based pre-coating maintains sufficient bonding strength while having good biodegradability.
[0067] In this invention, the starch-based pre-coating layer is preferably prepared from a starch-based pre-coating liquid, and the solid content of the starch-based pre-coating liquid is preferably 45-55%. Preferably, the modified starch, filler, lubricant, and water are mixed to obtain the starch-based pre-coating liquid.
[0068] In this invention, the heat-sensitive color-developing layer preferably comprises 3-(3-tolylureo)phenyl-4-methylbenzenesulfonate (PF201), a BPA-free color-developing system that completely replaces traditional BPA or BPS color-developing agents. PF201 is a commercially available, mature non-phenolic color-developing agent that does not produce estrogenic activity and complies with the EU (EU) 2024 / 3190 regulation's requirement for a complete ban on BPA in food contact materials.
[0069] In this invention, the heat-sensitive color-developing layer is preferably made of a color-developing coating, and the color-developing coating is preferably made by a method comprising the following steps: (a) A leuco dye paste is provided, wherein the leuco dye paste preferably comprises the following components in parts by weight: 10-12 parts by weight of ODB-2 (2-phenylamino-3-methyl-6-dibutylaminofluorane), 16-18 parts by weight of polyvinyl alcohol (PVA, used in the form of a 20 wt% aqueous solution, based on polyvinyl alcohol), 0.5 parts by weight of dispersant NNO (sodium methylene bis(naphthalene)sulfonate), and 44-46 parts by weight of water; (b) Provide a color developer slurry, wherein the color developer slurry preferably comprises the following components in parts by weight: 35-38 parts by weight of PF201 color developer, 16-18 parts by weight of polyvinyl alcohol (used in the form of a 20 wt% aqueous solution, based on polyvinyl alcohol), 0.5 parts by weight of dispersant NNO, and 44-46 parts by weight of water; (c) Color-developing coating: 20-22 parts by weight of the leuco dye paste, 36-38 parts by weight of the color developer paste, 24-26 parts by weight of polyvinyl alcohol (used in the form of a 10wt% aqueous solution, calculated as an aqueous solution), 10-15 parts by weight of the filler slurry (kaolin slurry, 30% solid content, calculated as kaolin slurry), 8-12 parts by weight of the hollow sphere emulsion (plastic pigment, 25% solid content, particle size 1.5μm, calculated as hollow sphere emulsion), 3-5 parts by weight of the sensitizer DPE (1,2-diphenyloxyethylene), 1-2 parts by weight of zinc stearate and 20-30 parts by weight of water.
[0070] In this invention, the effective component of the hollow sphere emulsion is preferably a cross-linked styrene-acrylate copolymer or polystyrene microspheres, with a hollow internal structure and an outer layer of polymer shell.
[0071] In a specific embodiment of the present invention, the leuco dye paste comprises the following components in parts by weight: 11 parts by weight of ODB-2, 17 parts by weight of PVA, 0.5 parts by weight of NNO, and 45 parts by weight of deionized water; the color developer paste comprises the following components in parts by weight: 36.5 parts by weight of PF201, 17 parts by weight of PVA, 0.5 parts by weight of NNO, and 45 parts by weight of deionized water; the color-developing coating comprises the following components in parts by weight: 21 parts by weight of leuco dye paste, 37 parts by weight of color developer paste, 25 parts by weight of 10wt% aqueous solution of PVA, 12 parts by weight of kaolin filler slurry (30% solid content), 10 parts by weight of hollow sphere emulsion (25% solid content, particle size 1.5μm, polystyrene microspheres), 4 parts by weight of sensitizer DPE, 1.5 parts by weight of zinc stearate, and 25 parts by weight of deionized water.
[0072] In this invention, the PVA in the color-developing coating and the modified starch in the starch-based pre-coating form a composite adhesive system. The PVA provides film-forming properties and color reaction stability, while the modified starch introduces degradable components, increasing the biodegradability of the thermosensitive color-developing layer to over 60%. The sensitizer DPE has a melting point of 98-100°C, melts at the thermosensitive printing temperature (80-120°C), and promotes the contact reaction between the PF201 color developer and the ODB-2 dye, enabling the color density of the thermosensitive color-developing layer to reach 1.0-1.2 at 120°C, meeting the requirements of commercial thermosensitive printing.
[0073] In this invention, the thermal base paper is preferably 53g / m² certified by FSC Forest Certification. 2 Or 58g / m 2 The thermal base paper, preferably 58g / m² certified by FSC forest certification, is preferred. 2The thermal base paper is preferably made of 100% natural cellulose, which is completely biodegradable in soil and compost environments. The surface of the thermal base paper is treated with micron-level coating to ensure uniform adhesion and rapid response of the thermal color-developing layer. The pH value of the thermal base paper is preferably 6.5~7.5 to avoid interference from acidity and alkalinity on the stability of thermal color development and the biodegradation process. The tear strength is preferably ≥180mN, and the stiffness is moderate, taking into account both die-cutting processability and end-labeling performance.
[0074] In this invention, the glassine paper is preferably 36~80 g / m² that has passed FSC certification. 2 White glassine paper, preferably 60g / m² certified by FSC. 2 White glassine paper.
[0075] In this invention, the solvent-free silicone oil layer (also known as the release layer) is preferably formed by thermal curing of a solvent-free silicone oil coating. More preferably, the solvent-free silicone oil coating is uniformly coated on the surface of the glassine paper using a coating machine. After thermal curing, a layer of the solvent-free silicone oil layer is formed on the surface of the glassine paper. The solvent-free silicone oil layer and the glassine paper together constitute FSC-certified white glassine release paper.
[0076] In this invention, the thermosetting temperature is preferably 105~170℃, specifically 105, 120, 150 or 170℃, and the time is preferably 2~8s, specifically 2, 3, 4, 6 or 8s.
[0077] The present invention does not have any particular limitation on the solvent-free silicone oil coating, and any type known to those skilled in the art can be used.
[0078] In this invention, the solid content of the solvent-free silicone oil layer is preferably 100%, and no VOC emissions are generated.
[0079] In this invention, the release force of the solvent-free silicone oil layer is preferably 5~10gf / 25mm, specifically 8gf / 25mm, and the residual adhesion rate is preferably ≥85%.
[0080] In this invention, the solvent-free silicone oil layer in the thermal paper self-adhesive is preferably 0.5~1.0wt%, which is lower than the 1% limit for non-compostable components in the EN13432 standard, and does not affect the compostability certification of the overall product.
[0081] The biodegradability (180 days) of the thermal paper self-adhesive described in this invention is preferably >98%, and the overall degradability is preferably >90%, more preferably >92%, meeting the EN 13432 industrial composting certification requirements.
[0082] The thermal paper self-adhesive of this invention adopts a fully bio-based material system. Through a composite structure of starch-based pre-coating, BPA-free thermal color-developing layer, BOPLA film protective layer, starch-based pressure-sensitive adhesive, solvent-free silicone oil layer, and white glassine paper, the overall environmentally friendly and biodegradable thermal paper self-adhesive product is achieved. It is suitable for applications with high environmental and safety requirements, such as food labels and fruit labels. Details are as follows: 1. Overall product structure innovation: For the first time, starch-based pre-coating + PF201 BPA-free color development layer + BOPLA protective layer + starch-based pressure-sensitive adhesive + FSC-certified white glassine release paper are combined into a complete thermal paper self-adhesive product, with each layer working together to achieve overall biodegradability.
[0083] 2. Innovation in starch-based pressure-sensitive adhesive formulation: specific ratio of oxidized starch to acrylate monomers, introduction of IA / HEMA functional monomers, bio-based tackifying system of hydrogenated rosin glycerol esters, and biodegradable crosslinking system of citric acid / tartaric acid.
[0084] 3. Innovative soap-free emulsion graft copolymerization process: Graft copolymerization is carried out at a low temperature of 60~65℃ using an APS / SBS redox initiation system, which is different from the existing cerium salt high-temperature initiation system, reducing energy consumption and reducing starch retrogradation.
[0085] 4. Innovative coating process for BOPLA protective layer: Starch-based pressure-sensitive adhesive is used as the bonding layer between the BOPLA film and the thermal paper color layer, achieving thermal bonding at a low temperature of 80~100℃, avoiding thermal deformation of the BOPLA film, and ensuring the overall biodegradability of the protective layer.
[0086] The present invention also provides the application of the thermal paper self-adhesive, which is used for food labels and / or fruit labels.
[0087] The present invention also provides a method for preparing the thermal paper self-adhesive described in the above technical solution, comprising a thermal paper surface material preparation section and a self-adhesive lamination section, to obtain the thermal paper self-adhesive.
[0088] In this invention, the thermal paper surface material preparation section preferably includes the following steps: The starch-based pre-coating liquid is applied to the surface of the thermal base paper and then dried to obtain the starch-based pre-coating layer. The color-developing coating is applied to the surface of the starch-based pre-coating layer and then dried to obtain the heat-sensitive color-developing layer; The adhesive surface of the BOPLA film protective layer is subjected to corona treatment, and a starch-based coating adhesive is applied to the surface of the corona-treated adhesive surface, and then cured to obtain the starch-based coating adhesive layer. The starch-based coating layer is bonded to the thermosensitive color-developing layer to obtain the thermosensitive paper surface material, which is composed of a BOPLA film protective layer, a starch-based coating layer, a thermosensitive color-developing layer, a starch-based pre-coating layer, and a thermosensitive base paper from top to bottom.
[0089] The present invention involves coating the starch-based pre-coating liquid onto the surface of the thermal base paper and then drying it to obtain the starch-based pre-coating layer.
[0090] In this invention, the coating amount of the starch-based pre-coating liquid is preferably 3~5 g / m³, based on dry weight. 2 Specifically, it can be 4g / m 2 The drying temperature is preferably 80~120℃, specifically 100℃, and a porous pre-coating is formed after the drying is completed; the coating is preferably done using a doctor blade / air knife coating machine.
[0091] After obtaining the starch-based pre-coating layer, the present invention applies the color-developing coating to the surface of the starch-based pre-coating layer and then dries it to obtain the heat-sensitive color-developing layer.
[0092] In this invention, the coating amount of the color-developing layer is preferably 5~8 g / m² (dry weight). 2 Specifically, it can be 6.5g / m 2 The drying process is preferably multi-stage drying, with the temperatures of the multi-stage drying preferably sequentially ranging from 80 to 100 to 120°C. The holding time for each stage is preferably 10 to 20 seconds, and the heating rate is preferably 15 to 25°C / min. After the drying process, a porous pre-coating layer is formed. The coating process is preferably roller coating, and more preferably using a roller coating machine. The coating temperature is preferably 25±2°C, and the humidity is preferably 50±5%.
[0093] The present invention performs corona treatment on the adhesive surface of the BOPLA film protective layer, applies a starch-based coating adhesive paste to the surface of the corona-treated adhesive surface, and then cures it to obtain the starch-based coating adhesive layer.
[0094] In this invention, the surface tension of the coated surface after corona treatment is preferably 38~42 dyn / cm.
[0095] In this invention, the parameters of the corona treatment preferably include: a treatment power of 2~10kW / m, a power supply frequency of 10~25kHz, and a surface tension of the substrate after treatment preferably of 38~42mN / m.
[0096] In this invention, the coating amount of the starch-based coating adhesive is preferably 3-5 g / m³, based on dry weight. 2The curing is preferably drying, and the drying temperature is preferably 80~120℃, specifically 100℃; the starch-based coating adhesive is preferably the starch-based pressure-sensitive adhesive.
[0097] After obtaining the starch-based coating layer and the thermosensitive color-developing layer, the present invention laminates the starch-based coating layer and the thermosensitive color-developing layer to obtain the thermosensitive paper surface material, which is composed of a BOPLA film protective layer, a starch-based coating layer, a thermosensitive color-developing layer, a starch-based pre-coating layer, and a thermosensitive base paper from top to bottom.
[0098] In this invention, the bonding temperature between the starch-based coating adhesive layer and the heat-sensitive color-developing layer is preferably 80~100℃, specifically 90℃, and the pressure is preferably 2~4 kg / cm². 2 Specifically, it can be 3kg / cm 2 The bonding is preferably performed by heat-bonding film application.
[0099] In this invention, the self-adhesive lamination process preferably includes the following steps: The solvent-free silicone oil coating is applied to the surface of glassine paper and then heat-cured to obtain the solvent-free silicone oil layer. After coating the surface of the solvent-free silicone oil layer with the environmentally friendly biodegradable starch-based pressure-sensitive adhesive and drying it, the environmentally friendly biodegradable starch-based pressure-sensitive adhesive layer is obtained. The thermal paper surface material is laminated with the environmentally friendly biodegradable starch-based pressure-sensitive adhesive layer to obtain the environmentally friendly biodegradable thermal paper self-adhesive.
[0100] The present invention obtains the solvent-free silicone oil layer by heat curing after the solvent-free silicone oil coating is applied to the surface of glassine paper.
[0101] In this invention, the amount of solvent-free silicone oil coating used is preferably 1.0~1.2 g / m³, based on dry silicon content. 2 .
[0102] In this invention, the temperature and time of the thermosetting are preferably the same as those described above, and will not be repeated here.
[0103] After obtaining the solvent-free silicone oil layer, the present invention coats the surface of the solvent-free silicone oil layer with the starch-based pressure-sensitive adhesive and then dries it to obtain the starch-based pressure-sensitive adhesive layer.
[0104] In this invention, the coating amount of the starch-based pressure-sensitive adhesive is preferably 15~22 g / m² (dry weight). 2 Specifically, it can be 18g / m 2 The drying temperature is preferably 100~120℃, specifically 100℃; the coating is preferably done using a comma-shaped doctor blade coater.
[0105] After obtaining the starch-based pressure-sensitive adhesive layer and the thermal paper face material, the present invention presses the thermal paper face material (with the BOPLA film protective layer facing upward) with the starch-based pressure-sensitive adhesive layer to obtain the thermal paper self-adhesive.
[0106] In this invention, the pressing pressure is preferably 2~4 kg / cm². 2 Specifically, it can be 3kg / cm 2 .
[0107] The technical solutions of this invention will be clearly and completely described below with reference to the embodiments thereof. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.
[0108] The test follows the standard: Static color density (120℃): Tested according to GB / T 28210-2024 "Thermal Paper"; initial tack was determined according to GB / T4852-2002 "Pressure-sensitive Adhesive Tape Initial Tack Test Method (Rolling Ball Method)"; 90° peel strength was tested according to FINAT FTM2 method; holding power (1kg weight) was determined according to GB / T 4851-2014 "Adhesive Tape Holding Power Test Method"; biodegradability (180 days) was determined according to EN 13432:2000 "Packaging - Packaging recycled by composting and biodegradation - Final packaging acceptance test program and evaluation criteria" (or equivalent to ISO 14855-1 "Determination of carbon dioxide emissions under controlled composting conditions").
[0109] Example 1 The thermal paper self-adhesive, from top to bottom, includes a biaxially oriented polylactic acid (BOPLA) film protective layer, a starch-based coating adhesive layer, a thermal color-developing layer, a starch-based pre-coating layer, a thermal base paper, a starch-based pressure-sensitive adhesive layer, a solvent-free silicone oil layer, and white glassine paper, which are stacked sequentially. The starch-based coating adhesive layer and the starch-based pressure-sensitive adhesive layer contain starch-based pressure-sensitive adhesive. The preparation method is divided into two main sections: the thermal paper surface material preparation section and the self-adhesive lamination section.
[0110] The thermal paper surface material preparation process includes the following steps: Preparation of thermal paper surface material: FSC certified 58g / m² material was selected. 2 Thermal base paper. Starch-based pre-coating solution formulation: 30 parts by weight of phosphated starch, 70 parts by weight of kaolin, 3.5 parts by weight of zinc stearate, and 103.5 parts by weight of deionized water, prepared into a coating solution with a solid content of 50%. The dry weight of the starch-based pre-coating solution on the surface of the thermal base paper is 4 g / m². 2The drying temperature is 100℃ to obtain a starch-based pre-coating.
[0111] The formulation of the color-developing layer coating is as follows: 21 parts by weight of leuco dye paste (comprising 11 parts by weight of ODB-2 + 17 parts by weight of PVA + 0.5 parts by weight of NNO + 45 parts by weight of deionized water), 37 parts by weight of color developer paste (36.5 parts by weight of PF201 + 17 parts by weight of PVA + 0.5 parts by weight of NNO + 45 parts by weight of deionized water), 25 parts by weight of PVA 10wt% aqueous solution, 12 parts by weight of kaolin filler slurry (30% solid content), 10 parts by weight of hollow sphere emulsion (25% solid content, particle size 1.5μm, polystyrene microspheres), 4 parts by weight of sensitizer DPE, 1.5 parts by weight of zinc stearate, and 25 parts by weight of deionized water. The anilox roller coating amount of the starch-based pre-coated surface color-developing layer coating is 6.5 g / m². 2 The drying temperature curve is 80→100→120℃, and the heat-sensitive color-developing layer is obtained.
[0112] BOPLA film protective layer: A 20μm thick BOPLA film undergoes corona treatment. A starch-based coating adhesive is then applied to the corona-treated surface. The surface tension of the corona-treated surface is 38 dyn / cm, and the dry weight of the starch-based coating adhesive is 4 g / m². 2 Bonding temperature 90℃, pressure 3kg / cm 2 A starch-based coating layer is formed to obtain a thermal paper surface material; the starch-based coating slurry is the same as that of starch-based pressure-sensitive adhesive, and the preparation method is described below for the preparation of starch-based pressure-sensitive adhesive.
[0113] Preparation of starch-based pressure-sensitive adhesive: The raw materials include: 20 parts by weight of oxidized cassava starch, 38 parts by weight of BA, 15 parts by weight of 2-EHA, 5 parts by weight of MMA (the mass ratio of oxidized starch to acrylate monomers is 1:2.79), 2.5 parts by weight of IA, 2 parts by weight of HEMA, 0.4 parts by weight of APS, 0.15 parts by weight of SBS, 90 parts by weight of deionized water, 0.3 parts by weight of polydimethylsiloxane defoamer, a tackifying resin system (including 10 parts by weight of hydrogenated rosin glycerol ester, 17 parts by weight of deionized water, and 0.4 parts by weight of dodecyl glycoside), and a biodegradable crosslinking agent (including 0.8 parts by weight of anhydrous citric acid, 0.3 parts by weight of tartaric acid, and 2.5 parts by weight of deionized water); the preparation method is as follows: Step 1: Gelatinization and activation of oxidized cassava starch. Oxidized cassava starch and 63 parts by mass of deionized water were added to a reaction vessel, and stirring was started (200 rpm). The temperature was raised to 85°C and kept at that temperature for 40 min to allow the starch to fully gelatinize and swell. Then the temperature was lowered to 55°C to obtain a gelatinized starch system. Step 2: Monomer pre-emulsification and grafting reaction. BA, 2-EHA, MMA, IA, and HEMA were pre-mixed to form a monomer phase. APS was dissolved in 5 times its mass of deionized water, and SBS was dissolved in 3 times its mass of deionized water, for later use. 30 wt% of the monomer phase was added to the gelatinized starch system at once, and stirred for 15 min to allow the monomers to diffuse into the starch molecular chains. Simultaneously, the remaining 70 wt% of the monomer phase and the APS aqueous solution were added dropwise (controlling the dropwise addition time to 2.5 minutes). The SBS aqueous solution was added dropwise simultaneously 1 hour after the monomer addition began (controlling the dropwise addition time to 1.5 minutes). The reaction temperature was maintained at 60℃. After the addition was complete, the mixture was kept at this temperature for 2 h, and then 0.05 parts by mass of APS was added to eliminate residual monomers, yielding a grafted copolymer emulsion. Step 3: Blending of thickening resins. Hydrogenated rosin glycerol ester was heated and melted (120℃). Deionized water and dodecyl glycoside were added at 70℃, and the mixture was sheared at 3000 r / min for 10 min to prepare an aqueous resin dispersion (thickening resin system). The resin dispersion was added to the graft copolymer emulsion under stirring, the temperature was lowered to 45℃, and the mixture was stirred for 30 min to obtain the emulsion. Step 4: Degradable crosslinking and conditioning. Citric acid and tartaric acid are dissolved in deionized water to obtain a degradable crosslinking agent. This agent is added to the emulsion obtained in Step 3 and stirred for 15 minutes. The pH is adjusted to 6.5 with ammonia, and an antifoaming agent is added. The mixture is stirred for 15 minutes, and then filtered through a 200-mesh filter to obtain a starch-based pressure-sensitive adhesive.
[0114] Self-adhesive lamination: Applying solvent-free silicone oil coating (platinum catalytic system) to a 60g / m² layer. 2 The surface of FSC-certified white glassine paper (with a solvent-free silicone coating, the dry silicone content is 1.1 g / m²) 2 After heat curing (120℃, 2s), the solvent-free silicone oil layer is obtained, with a release force of 8gf / 25mm; a coating (coating dry weight of 18g / m²) is then applied to the surface of the solvent-free silicone oil layer. 2 The starch-based pressure-sensitive adhesive is dried at 100°C to obtain the starch-based pressure-sensitive adhesive layer; the thermal paper surface material is then pressed together with the starch-based pressure-sensitive adhesive layer at a pressure of 3 kg / cm². 2 The thermal paper adhesive is obtained.
[0115] The performance test results are as follows: BPA content was not detected; food contact compliance complies with EU 2024 / 3190.
[0116] Example 2 The preparation method of Example 1 is the same as that of Example 1, except that 18 parts by weight of oxidized cassava starch, 35 parts by weight of BA, 12 parts by weight of 2-EHA and 2 parts by weight of MMA are used, that is, the mass ratio of oxidized starch to acrylate monomer system is 1:2.7.
[0117] The performance test results are as follows: static color density (120℃) is 1.12; initial tack is 12 ball; 90° peel strength is 7.8 N / 25mm; holding power (1kg weight) is 18h; biodegradability (180 days) is 98.5%; BPA content was not detected; the overall biodegradable material content is 93.2wt%; food contact compliance complies with EU 2024 / 3190.
[0118] Example 3 The preparation method of Example 1 is the same as that of Example 1, except that 22 parts by mass of oxidized cassava starch, 45 parts by mass of BA, 19 parts by mass of 2-EHA, and 9 parts by mass of MMA are used, that is, the mass ratio of oxidized starch to acrylate monomer system is 1:3.3.
[0119] The performance test results are as follows: static color density (120℃) is 1.18; initial tack is 15 ball; 90° peel strength is 9.2 N / 25mm; holding power (1kg weight) is 28h; biodegradability (180 days) is 97.5%; BPA content was not detected; the overall biodegradable material content is 91.8wt%; food contact compliance complies with EU 2024 / 3190.
[0120] Example 4 Referring to the preparation method of Example 1, this example differs from Example 1 only in that the amount of hydrogenated rosin glycerol ester in the tackifying resin system formulation is changed, and different pressure-sensitive adhesive samples are prepared, as shown in Table 1 below. It can be seen that as the amount of hydrogenated rosin glycerol ester increases from 6 parts by mass to 14 parts by mass, the initial tack increases from ball size 10 to ball size 16, and the 90° peel strength increases from 6.2 N / 25 mm to 10.2 N / 25 mm, indicating that the amount of tackifying resin is positively correlated with the initial tack and peel performance of the pressure-sensitive adhesive. When the amount is 10 parts by mass (Example 1), the initial tack reaches ball size 14 and the peel strength is 8.5 N / 25 mm, meeting the requirements for label applications. When the amount is too low (6 parts by mass), the initial tack and peel strength are insufficient; when the amount is too high (14 parts by mass), although the pressure-sensitive performance is further improved, the contribution of the tackifying resin to biodegradability decreases, and the cost increases. Therefore, selecting 8 to 12 parts by weight of hydrogenated rosin glycerol ester can achieve the best balance between pressure-sensitive properties and environmentally friendly biodegradability.
[0121] Table 1. Formulation and performance test results of the tackifying resin system
[0122] Example 5: Performance Influence of Different Biodegradable Crosslinking Agent Formulations Referring to the preparation method of Example 1, this example differs from Example 1 only in that the amounts of citric acid and tartaric acid in the biodegradable crosslinking agent formulation are changed, and four samples are prepared with no crosslinking agent, low amount, medium amount (Formula of Example 1), and high amount, respectively. These are shown in Table 2 below. It can be seen that: (1) When no crosslinking agent is added (sample 5-1), although the biodegradation rate is the highest at 180 days (99.2%), the holding power is only 2 hours, which cannot meet the label application requirements; (2) With the increase of citric acid / tartaric acid dosage, the holding power is significantly improved, from 12 hours (sample 5-2) to 38 hours (sample 5-4), the biodegradation rate at 180 days decreases slightly, but still remains above 97.2%; (3) When citric acid is 0.8 parts by weight and tartaric acid is 0.3 parts by weight (Example 1, i.e., sample 5-3), the holding power is 24 hours and the biodegradation rate is 98.0%, achieving the best balance between pressure sensitivity and degradability; (4) When the crosslinking agent dosage is too high, although the holding power is further improved to 38 hours, the increase in peel strength slows down, and the decrease in biodegradation rate increases. Therefore, the crosslinking agent formulation with 0.8 parts by weight of anhydrous citric acid and 0.3 parts by weight of tartaric acid can achieve the best balance between pressure sensitivity and degradability.
[0123] Table 2. Biodegradable crosslinking agent formulation and performance test results
[0124] Comparative Example 1: Traditional thermal paper self-adhesive As a comparison, thermal paper self-adhesive was prepared using traditional techniques: thermal base paper 58g / m² 2 The pre-coating layer uses styrene-butadiene rubber latex adhesive, the color-developing layer uses BPA colorant, the protective layer uses polyethylene wax coating, the pressure-sensitive adhesive uses traditional solvent-based acrylic pressure-sensitive adhesive (starch-free), and the glassine release paper uses solvent-based silicone oil coating. The preparation method is described in Example 1.
[0125] Comparative Example 2: The mass ratio of oxidized starch to acrylate monomer was too low (<1:2.7). Referring to the preparation method of Example 1, the difference between this comparative example and Example 1 is that 25 parts by weight of oxidized cassava starch, 30 parts by weight of BA, 10 parts by weight of 2-EHA, and 3 parts by weight of MMA (starch: acrylate monomer mass ratio = 1:1.72).
[0126] The results are as follows: static color density (120℃) is 1.14; initial tack is 8-ball; 90° peel strength is 5.5 N / 25mm; holding power (1kg weight) is 6h; biodegradability (180 days) is 99.0%; and the overall biodegradable material percentage is 94.5%.
[0127] In this comparative example, the excessively high proportion of oxidized cassava starch and insufficient amount of acrylate monomers resulted in a low proportion of acrylate segments in the graft copolymer, failing to form an effective viscoelastic network for the pressure-sensitive adhesive. The initial tack of the pressure-sensitive adhesive was only that of an 8-ball, the peel strength was only 5.5 N / 25 mm, and the holding power was only 6 h. All three key performance indicators were significantly lower than those of Example 1 (14-ball, 8.5 N / 25 mm, 24 h), failing to meet the basic requirements for label adhesion. Although the biodegradation rate was as high as 99.0%, the grafting efficiency and pressure-sensitive performance were severely mismatched, proving that when the mass ratio of oxidized starch to acrylate monomers was less than 1:2.7, it was impossible to simultaneously meet the balance between grafting efficiency and environmentally friendly degradation rate.
[0128] Comparative Example 3: The mass ratio of oxidized starch to acrylate monomer was too high (>1:3.3). Referring to the preparation method of Example 1, the difference between this comparative example and Example 1 is that 15 parts by weight of oxidized cassava starch, 50 parts by weight of BA, 22 parts by weight of 2-EHA, and 1 part by weight of MMA (starch: acrylate monomer mass ratio = 1:5.53).
[0129] The results are as follows: static color density (120℃) is 1.16; initial tack is 17 ball; 90° peel strength is 11.5 N / 25 mm; holding power (1 kg weight) is 42 h; biodegradability (180 days) is 85.2%; and the overall biodegradable material percentage is 88.6%.
[0130] In this comparative example, due to the excessively high amount of acrylate monomers (1:5.53), although the initial tack (17-ball), peel strength (11.5 N / 25 mm), and holding power (42 h) of the pressure-sensitive adhesive were all higher than those of Example 1, the biodegradability rate decreased to 85.2%, and the overall proportion of biodegradable material decreased to 88.6%, which is lower than the 90% target threshold of this invention. The excessively high proportion of acrylate monomers increased the content of petrochemical-based non-degradable components, causing the product to fail to meet the requirement of "biodegradability rate >90% in 6 months" in EN 13432 industrial composting certification. Therefore, when the mass ratio of oxidized starch to acrylate monomers is higher than 1:3.3, although the pressure-sensitive performance is improved, the environmental degradation rate does not meet the standard, and the design goal of this invention cannot be achieved.
[0131] Comparative Example 4: Performance Effects of Different Doses of IA / HEMA Referring to the preparation method of Example 1, this comparative example differs from Example 1 only in that the amount of functional monomers IA and HEMA is changed, and four samples are prepared respectively: no IA and no HEMA, only IA, only HEMA, and high IA and high HEMA. The other components and process conditions remain unchanged, as shown in Table 3 below. It can be seen that: (1) Without the addition of IA and HEMA (sample 6-1), the initial tack is high (ball 16) and the peel strength is also high (9.5 N / 25 mm), but the holding power is only 3h, which cannot meet the requirements for long-term label adhesion; (2) With the addition of only IA (sample 6-2), the introduction of carboxyl groups improves the cohesive strength of the pressure-sensitive adhesive, and the holding power increases to 10h, but the initial tack decreases (ball 15); (3) With the addition of only HEMA (sample 6-3), the introduction of hydroxyl groups enhances the crosslinking density, and the holding power increases to 16h, but the initial tack and peel strength decrease significantly (ball 13, 7.8 N / 25 mm); (4) With the addition of 2.5 parts by weight of IA and 2 parts by weight of HEMA (Example 1, i.e., sample 6-4), the carboxyl and hydroxyl groups have a synergistic effect, the holding power is significantly increased to 24h, the initial tack is maintained at ball 14, and the peel strength is 8.5. N / 25mm, achieving a balance of three key performance aspects; (5) When the amount of IA and HEMA is too high (sample 6-5), the crosslinking density is too high, resulting in a significant decrease in initial tack and peel strength (ball No. 11, 7.2N / 25mm). Although the holding power is as high as 48h, the initial tack performance no longer meets the basic requirements for label application. Therefore, the optimal balance of pressure-sensitive adhesive performance is achieved with 2.5 parts by weight of IA and 2 parts by weight of HEMA.
[0132] Table 3 Functional monomer formulations and performance test results
[0133] Test results show that the thermal paper self-adhesive of Example 1 has a color density (1.15) close to that of Comparative Example 1 (1.25), meeting the requirements for commercial thermal printing. Regarding pressure-sensitive adhesive performance, it exhibits an initial tack of 14 balls, a peel strength of 8.5 N / 25 mm, and a holding power of 24 hours, meeting the basic requirements for label applications. In terms of environmental performance, it has a biodegradability rate of 98% (180 days), with an overall biodegradable material content exceeding 92%, and is completely BPA-free, complying with EU food contact material regulations. Compared to the comparative example, this invention achieves a significant improvement in environmental friendliness while maintaining usable pressure-sensitive performance.
[0134] Toxicity tests were conducted on the product of Example 1 and the conventional product, and the results are shown in Table 4. It can be seen that the present invention achieves intrinsic safety in terms of the toxicity of the color developer and the adhesive system, eliminating the endocrine disruption risk of BPA / BPS.
[0135] Table 4 Comparison of Product Toxicity
[0136] The degradation rate of the product in Example 1 and the conventional product was tested, and the results are shown in Table 5. It can be seen that the introduction of starch into the PVA and modified starch composite system can significantly improve the degradation of PVA (microorganisms preferentially consume starch, forming a local microenvironment that promotes the breakage of PVA chains).
[0137] Table 5 Comparison of Degradable Rates
[0138] Synchronous degradation of each layer in Example 1 Under industrial composting conditions (58±2℃, aerobic microorganisms), the degradation of the eight-layer structure exhibited significant asynchronous behavior, as shown in Table 6. The degradation time was: 1-2 weeks: Thermal base paper + white glassine paper + starch-based pre-coating + starch-based film coating layer → rapid disintegration period; 3-4 weeks: The BOPLA film begins to crack, and the structure of the thermosensitive color layer becomes loose; Weeks 8-12: BOPLA film continues to hydrolyze, and starch components in the heat-sensitive color-developing layer are degraded in large quantities; Weeks 12-24: The starch segments in the pressure-sensitive adhesive layer degrade preferentially, while the acrylate segments mineralize slowly; 24+ weeks: The silicone oil layer remains almost unchanged (physically dispersed in the compost).
[0139] Table 6. Synchronicity of Degradation of Each Layer
[0140] The impact of synchronicity on standard compliance Disintegration test (12 weeks): EN 13432 requires ≤10% residue after 12 weeks through a 2mm sieve. Since the first and second tier materials can fully disintegrate within 12 weeks, the physical disintegration index can be passed even if the pressure-sensitive adhesive layer and silicone oil are not completely degraded. The silicone oil disperses in the form of tiny droplets and does not form fragments >2mm.
[0141] Biodegradation rate test (180 days): The overall degradation rate can reach >90%, meeting all standards.
[0142] The key role of cross-linking systems in synchronization Pressure-sensitive adhesives use a biodegradable crosslinking system of citric acid / tartaric acid, which differs from traditional isocyanate / epoxy crosslinking. The cross-linked ester bonds of citric acid can be hydrolyzed by microorganisms in composting, gradually releasing starch molecular chains and acrylate segments without forming a permanent cross-linking barrier; If a non-degradable crosslinking agent is used, the pressure-sensitive adhesive layer will form a plastic core, and even if the outer layer completely disintegrates, microplastics will remain inside for a long time.
[0143] The standard compliance of the embodiments of the present invention is shown in Table 7.
[0144] Table 7 Standard Compliance
[0145] In summary: The present invention has the following beneficial effects: (1) Overall biodegradability: All layers of the product are made of bio-based or biodegradable components, with biodegradable materials accounting for more than 90% of the total. Among them, FSC paper base (100% cellulose), starch-based pre-coating (modified starch), BOPLA film (polylactic acid), and starch-based pressure-sensitive adhesive (starch graft copolymer) are all biodegradable materials. Only the solvent-free silicone oil layer (accounting for <1%) is a non-degradable component, which meets the requirement of EN 13432 industrial composting certification that the content of non-compostable components is less than 1%.
[0146] (2) Food contact safety: PF201 non-phenolic color developer is used to completely replace BPA / BPS. The estrogenic activity of PF201 is 2-3 orders of magnitude lower than that of BPA, which meets the requirements of the EU (EU) 2024 / 3190 regulation to completely ban BPA in food contact materials, as well as the requirements of the Chinese GB 4806 series standards. It can be safely used in applications such as fruit labels that come into direct contact with food.
[0147] (3) By adjusting the mass ratio of oxidized starch to acrylate monomers to 1:2.7~1:3.3, adopting the APS / SBS redox initiation system (different from cerium salt initiator), introducing IA / HEMA functional monomers, adopting the hydrogenated rosin glycerol ester + APG thickening system and citric acid / tartaric acid degradable crosslinking system, the starch-based pressure-sensitive adhesive can meet the balance between grafting efficiency and environmental degradation rate.
[0148] (4) Performance balance: Through the introduction of itaconic acid and HEMA functional monomers, the pressure-sensitive adhesive achieves a performance balance of initial tack (14 ball), peel strength (8.5N / 25mm) and holding power (24h) under the synergistic effect of carboxyl and hydroxyl groups, which meets the bonding requirements of disposable labels (such as fruit labels) under normal temperature and cold storage and transportation environments.
[0149] (5) Green manufacturing: The entire process adopts a water-based coating system and solvent-free silicone oil coating. The BOPLA film coating process has no VOC emissions, which meets the requirements of green manufacturing and clean production.
[0150] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a starch-based pressure-sensitive adhesive, characterized in that, Includes the following steps: Oxidized starch is gelatinized and activated to obtain a starch-based material system; The starch-based material system, acrylate monomer system, itaconic acid, hydroxyethyl methacrylate and initiator system are mixed and subjected to free radical graft copolymerization to obtain a graft copolymer emulsion, wherein the grafting rate of the graft copolymer in the graft copolymer emulsion is 70%~140%; The graft copolymer emulsion, the tackifying resin system and the biodegradable crosslinking agent are mixed and crosslinked to obtain the starch-based pressure-sensitive adhesive. The mass ratio of oxidized starch to acrylate monomer system used in preparing the starch-based material system is 1:2.7 to 1:3.3; the acrylate monomer system includes butyl acrylate, isooctyl acrylate, and methyl methacrylate. The initiator system includes persulfate and inorganic sulfur-based reducing agents; The tackifying resin system includes hydrogenated rosin glycerol ester and a bio-based nonionic emulsifier; The degradable crosslinking agents include citric acid and tartaric acid.
2. The preparation method according to claim 1, characterized in that, The mass ratio of oxidized starch, butyl acrylate, isooctyl acrylate and methyl methacrylate is 18~22:35~45:12~19:2~9.
3. The preparation method according to claim 1 or 2, characterized in that, The mass ratio of oxidized starch to itaconic acid is 18~22:2~3.
4. The preparation method according to claim 1 or 2, characterized in that, The mass ratio of oxidized starch to hydroxyethyl methacrylate is 18~22:1.5~2.
5.
5. The preparation method according to claim 1, characterized in that, The bio-based nonionic emulsifiers include dodecyl glycosides and / or tetradecyl glycosides.
6. The starch-based pressure-sensitive adhesive prepared by the preparation method according to any one of claims 1 to 5, characterized in that, The grafting rate of the starch-based pressure-sensitive adhesive is 70%~140%.
7. The application of the starch-based pressure-sensitive adhesive according to claim 6 in the field of thermal paper self-adhesive.
8. A thermal paper self-adhesive label, characterized in that, The material comprises a biaxially oriented polylactic acid film protective layer, a starch-based coating layer, a thermosensitive coloring layer, a starch-based pre-coating layer, a thermosensitive base paper, a starch-based pressure-sensitive adhesive layer, a solvent-free silicone oil layer, and glassine paper, which are stacked sequentially. The starch-based coating layer and the starch-based pressure-sensitive adhesive layer contain the starch-based pressure-sensitive adhesive as described in claim 6.
9. The thermal paper self-adhesive according to claim 8, characterized in that, The thermosensitive color-developing layer comprises 3-(3-tolylureo)phenyl-4-methylbenzenesulfonate.
10. The thermal paper self-adhesive according to claim 8, characterized in that, The starch-based pre-coating includes modified starch, fillers, and lubricants.